Acute effects of foam rolling and dynamic stretching on angle-specific change of direction ability, flexibility and reactive strength in male basketball players - Yuan, Haoxiang; Mao, Junjie; Lai, Canfeng; Lu, Haiping; Xue, Yadan; Liu, Qingshan (Biology of Sport, 2023)
The purpose of our study was to determine the acute effects of dynamic stretching (DS), foam rolling (FR) and foam rolling combined with dynamic stretching (Combo) protocols on angle-specific change of direction (COD) ability, drop jump (DJ) performance and flexibility. Using a counterbalance crossover study design, eleven male basketball collegiate players (20.7±0.6 years) were randomly assigned to one of the four protocols – control (CON), DS, FR, Combo – for each session, for a total of four sessions. A more aggressive foam cylinder with raised nodules, which is thought to be effective in stimulating the deep layer of muscle tissue, was used to observe for changes in their performance during sit and reach (SAR), DJ and COD tasks in 45 and 180 degrees. One-way repeated measures ANOVA was used to identify differences of each variable separately between interventions. The SAR after three interventions compared to the CON was significantly improved (F (3,30) = 5.903, P = 0.003, η 2 = 0.371). In the 505 test, both limbs failed to show a significant improvement in COD deficit. The non-dominant limb showed a significant improvement of 6.4% after FR when performing the Y-shaped agility (F (3,30) = 4.962, P = 0.0065 < 0.05, η 2 = 0.332). In the DJ, the reactive strength index and contact time changed significantly by 17.5% and -17.5% (η 2 = 0.518, η 2 = 0.571), respectively, immediately after FR. The current research suggested that FR may have an enhancing effect on COD speed in a 45° cutting task and neuromuscular function, while having the potential to improve non-dominant limb deficits in both COD tasks. In contrast, the Combo warm-up protocol did not produce a cumulative effect, suggesting the need for coaches to remain cautious about excessive warm-up duration.